Responsivitas Layanan dan Keamanan Layanan Digital terhadap Kepercayaan Konsumen di KS Agsa Collection Store Colomadu Karanganyar - Nanda Ayu Silviani; Indra Hastuti; Esti Dwi Rahmawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The advancement of digital technology has encouraged UMKM to utilize digital platforms for marketing and sales activities. In online transactions, consumer trust is a crucial factor, as consumers cannot physically inspect products or interact directly with sellers. This study aims to analyze the impact of service responsiveness and digital service security on consumer trust at KS Agsa Collection Store in Colomadu, Karanganyar. A quantitative approach with a causal-associative research design was employed. Data were collected via questionnaires distributed to 87 respondents selected through purposive sampling. Data analysis involved multiple linear regression, partial tests, simultaneous tests, and the coefficient of determination. The results indicate that both service responsiveness and digital service security have a positive and significant effect on consumer trust. Furthermore, the two variables jointly exert a significant influence on consumer trust. These findings demonstrate that fast, accurate, and responsive service, combined with secure digital transaction processes, can enhance consumer trust. The study implies that MSMEs need to continuously improve service responsiveness and maintain digital service security to strengthen consumer trust, boost customer loyalty, and ensure business sustainability in the digital era.